Galactic hail: the origin of the high-velocity cloud complex C. (17th December 2014) - Fraternali, F.; Marasco, A.; Armillotta, L.; Marinacci, F.
Abstract : High-velocity clouds consist of cold gas that appears to be raining down from the halo to the disc of the Milky Way. Over the past 50 years, two competing scenarios have attributed their origin either to gas accretion from outside the Galaxy or to circulation of gas from the Galactic disc powered by supernova feedback (galactic fountain). Here, we show that both mechanisms are simultaneously at work. We use a new galactic fountain model combined with high-resolution hydrodynamical simulations. We focus on the prototypical cloud complex C and show that it was produced by an explosion that occurred in the Cygnus-Outer spiral arm about 150 Myr ago. The ejected material has triggered the condensation of a large portion of the circumgalactic medium and caused its subsequent accretion on to the disc. This fountain-driven cooling of the lower Galactic corona provides the low-metallicity gas required by chemical evolution models of the Milky Way's disc.